Multispectral electroluminescence enhancement of single-walled carbon nanotubes coupled to periodic nanodisk arrays - Zakharko, Yuriy; Held, Martin; Graf, Arko; Zaumseil, Jana (Optics express, 2017)
The integration of periodic nanodisk arrays into the channel of a light-emitting field-effect transistor leads to enhanced and directional electroluminescence from thin films of purified semiconducting single-walled carbon nanotubes. The maximum enhancement wavelength is tunable across the near-infrared and is directly linked to the periodicity of the arrays. Numerical calculations confirm the role of increased local electric fields in the observed emission modification. Large current densities are easily achieved due to the high charge carrier mobilities of carbon nanotubes and will facilitate new electrically driven plasmonic devices.